2017
DOI: 10.1177/1462474517699814
|View full text |Cite
|
Sign up to set email alerts
|

Why punishment pleases: Punitive feelings in a world of hostile solidarity

Abstract: The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRAP url' above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 61 publications
2
53
0
Order By: Relevance
“…It targets the individual offender as well as his or her family and, as a collective penal ritual which ‘draws on norms of retributive justice’ (Garland, 2005: 799), is largely tolerated by both state and non-state actors (being only weakly policed or punished). As such, it enjoys a degree of legitimacy, albeit unstable and contested, in terms of which a ‘hostile solidarity’ (Carvalho and Chamberlen, 2018: 217) is engendered against ‘wrongdoers’ (Carvalho and Chamberlen, 2018: 225; Garland, 2005; Mead, 1918; Super, 2016b).…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…It targets the individual offender as well as his or her family and, as a collective penal ritual which ‘draws on norms of retributive justice’ (Garland, 2005: 799), is largely tolerated by both state and non-state actors (being only weakly policed or punished). As such, it enjoys a degree of legitimacy, albeit unstable and contested, in terms of which a ‘hostile solidarity’ (Carvalho and Chamberlen, 2018: 217) is engendered against ‘wrongdoers’ (Carvalho and Chamberlen, 2018: 225; Garland, 2005; Mead, 1918; Super, 2016b).…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…Regarding ethnicity, scholars of punishment disparities have demonstrated that regimes may rely on criminal justice institutions to establish the legitimacy of ethnically-dominated states (LaFree, 1998; Ruddell, 2005) as well as to oppress or exclude minority populations from participation in political action, formal labor markets, and other segments of civic society (Blackmon, 2008; Goffman, 2009; Uggen and Manza, 2002; Van Cleve, 2016; Wacquant, 2009; Wakefield and Uggen, 2010; Western and Pettit, 2010). Punishment may engender solidarity amongst groups represented by the punishers (Carvalho and Chamberlen, 2017; Durkheim, 1893/1997). Indeed, “tough-on-crime” rhetorics have been successful tools in securing white political support, reinforcing the notion that dominant ethnic groups mobilize carceral apparatuses to consolidate and legitimate control (Lynch, 2009; Sudbury, 2014).…”
Section: Ethnic Politics and State Powermentioning
confidence: 99%
“…Claims that punishment expresses helpless anxiety (Robinson and Gadd, 2016), aggressive impulses of sadism or self-assertion (Carvalho and Chamberlen, 2018; Mead, 1964 [1918]), envy and masochistic guilty desires for punishment (Garland, 1990; Maruna et al, 2004) or guilty feelings of complicity with the social causes of crime (Garland, 2001; Maruna et al, 2004), along with their rationalization, disowning or disavowal, are suggestive, but offered up unsystematically they give us little in the way of a deeper grasp of the symbolic unities and antinomies of penality. This is because they deploy abstractions from a psychoanalytic conception of soul ( psyche ), the core of which is, as Lear has argued, not the idea of an irrational unconscious mind but rather a distinctive conception of unconscious mindedness.…”
Section: The Priority Of Unconscious Phantasymentioning
confidence: 99%